1995
DOI: 10.1111/j.1399-3054.1995.tb00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence quenching and violaxanthin deepoxidation of FBPase antisense plants at low light intensities and low temperatures

Abstract: Genetically modified potato (Solanum tuberosum L. cv. Desiree) and tobacco (Nicotiana tabacum cv. Samsun N.N.) plants were used to analyze the effects exerted by the chloroplastic (cp) fructose‐ 1,6‐bisphosphatase (FBPase) on the regulation of light energy discrimination at the level of photosystem II. The cp‐FBPase activity was progressively inhibited by an mRNA antisense to this FBPase. The chlorophyll fluorescence quenching parameters of these transgenic plants were compared to those of wild‐type and transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…7 In addition, attention was drawn to an apparent concordance between the daily variation in tree stem diameter, dD, and the variation in the gravimetric tide, dg; 18,19 and, similarly, with the aid of the Etide program, Fisahn et al observed that roots of Arabidopsis thaliana appeared to perceive the lunisolar tidal acceleration, this perception being expressed in a tide-like variation in the rate of root elongation. 20 In continuation of work by Fisahn et al on chlorophyll fluorescence, 21 as initiated by Sachs, 2 the present study demonstrates a close correlation between the yield of chlorophyll fluorescence Ft derived from Photosystem II in Arabidopsis thaliana and the lunisolar tidal force. In particular, we tested the hypothesis that oscillations in the yield of chlorophyll fluorescence Ft emerging from the reaction centers of PSII under conditions of continuous illumination exhibit phase congruence and period synchrony with the lunisolar tidal force, as estimated by the Etide software application.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…7 In addition, attention was drawn to an apparent concordance between the daily variation in tree stem diameter, dD, and the variation in the gravimetric tide, dg; 18,19 and, similarly, with the aid of the Etide program, Fisahn et al observed that roots of Arabidopsis thaliana appeared to perceive the lunisolar tidal acceleration, this perception being expressed in a tide-like variation in the rate of root elongation. 20 In continuation of work by Fisahn et al on chlorophyll fluorescence, 21 as initiated by Sachs, 2 the present study demonstrates a close correlation between the yield of chlorophyll fluorescence Ft derived from Photosystem II in Arabidopsis thaliana and the lunisolar tidal force. In particular, we tested the hypothesis that oscillations in the yield of chlorophyll fluorescence Ft emerging from the reaction centers of PSII under conditions of continuous illumination exhibit phase congruence and period synchrony with the lunisolar tidal force, as estimated by the Etide software application.…”
Section: Introductionsupporting
confidence: 84%
“…1). 21,32 Continuous records of the current fluorescence yield Ft The current fluorescence yield, Ft, is continuously monitored in the Measure-mode of the Imaging-Pam when the measuring light (ML) is switched on. Ft images could be saved without the application of a saturating light pulse by operation of the "Ft only clock" option.…”
Section: Chlorophyll Fluorescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…At the start of each measurement, a plant was dark adapted for 20 min for determination of F o and F m (Bilger et al . 1995; Fisahn et al . 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Chlorophyll fluorescence imaging was performed by an IMAGING-PAM chlorophyll fluorometer (Heinz Walz GmbH, Effeltrich, Germany). At the start of each measurement, a plant was dark adapted for 20 min for determination of Fo and Fm Fisahn et al 1995).Then, the first level of PFD (4 mmol m -2 s -1 ) was applied and a set of values was measured. The same procedure was repeated for each PFD level (10,50,100,225,365,585 and 955 mmol m -2 s -1 ).…”
Section: Chlorophyll Fluorescence Imaging and Leaf Sample Harvestingmentioning
confidence: 99%